PROFIL PROTEIN PADA IKAN TENGGIRI DENGAN VARIASI PENGGARAMAN DAN LAMA PENGGARAMAN DENGAN MENGGUNAKAN METODE SDS-PAGE - Wahyudi, Riky; Maharani, Endang Tri Wahyuni (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The aim of this study is to describe protein profile based SDS-PAGE in Mackerel withsalting variation and salting time. Design of this study is experimental study withMackerel with concentration of salting 10%, 20%, 30%, b/b and times of salting 12hours, 24 hours and 36 hours asobjects of this study. Variations of saltingconcentration is worked with each variation of salting time. Protein profile ofMackerel is analyzed using 10 % SDS-PAGE method. The result of this study showsthat concentration of salting 10% b/b for 12 hours on Mackerel has more majorprotein bands than Mackerel which gets salting 20%, 30% b/b for 12 hours and 10%,20% dan 30% b/b for 24 hours and 36 hours while salting 30% b/b for 36 hours is notsuggested because all of major protein bands have denaturated to become thin majorprotein bands and minor protein bands. Keyword : Mackerel, Salting, Protein Profile, SDS-PAGE